ANALISIS KANDUNGAN ZAT BESI DAN DAYA TERIMA ALMOND CRISPY DENGAN VARIASI SUBSTITUSI TEPUNG DAUN KELOR (Moringa oleifera) - Oktafiani, Lirista Dyah Ayu; Aprilia, Sintia (Jurnal Gizi dan Pangan Soedirman, 2023)
The female body condition is declared anemic if the hemoglobin level is ˂12 mg/dL. Moringa leaf flour contains iron 28.2 mg/100 g so that it can be an alternative to overcome anemia of adolescent girls in substituting almond crispy. The purpose of this study was to analyze the iron content and acceptability of almond crispy with variations in moringa flour substitution of 0% (control), 5%, 10%, and 15%. This research design was quasi experimental and involved 30 adolescent girls as panelists. Iron content was analyzed using Kruskal Wallis and Mann Whitney tests and acceptability test using Friedman and Wilcoxon Sign Rank Test. The results of the analysis showed that there was a significant relationship between variables with more substitution of moringa flour, the iron content increased. The results of the analysis of the acceptability of moringa-substituted almond crispy on color, aroma, taste, and texture were most liked by 5% moringa flour substitution. Consumption of 12 pieces of almond crispy with 5% moringa flour substitution can fulfills 30.6% of the 2019 RDA of iron requirement for 1-time snacks in adolescent girls. Almond crispy meets the requirements in the aspects of odor, color, and taste according to SNI Biscuits 2973:2018.